Emergence, adoption, and implementation of collaborative wildlife parnerships in Kenya: A look at conditions for success - Mburu, John; Birner, Regina (Informa UK Limited, 2007)
This article explores the factors that contribute to the emergence and adoption of wildlife partnerships in Kenya. This is a management approach based on the concept of collaborative management (comanagement). In addition, the article analyzes two case studies and examines how successful the implementation of partnership projects has been in terms of stewardship, distributional aspects, and fulfilling conservation interests. The key factors found to favor wildlife partnerships include enabling policies, the presence of organizational capacity within user groups, and the access of local communities to benefits from wildlife through land ownership. Furthermore, it was found that the approach has had mixed success because important challenges emerged from its implementation. The article concludes by highlighting several implications for the future of wildlife partnerships in Kenya.